Low-income African American Women’s Cultural Models of Work: Implications for Adult Education - Elisabeth Hayes; Wendy Way (Adult Education Research Conference, 2000)
This study investigated how African American women from low-income, single-parent female-headed households conceptualize work and transitions to work, and how these conceptualizations relate to the dominant discourse of work underlying policies and practices in adult education. The findings challenge some prevalent assumptions and approaches in work-related education for low-income women.